Inosculation and Perfusion of Pre-Vascularized Tissue Patches Containing Aligned Human Microvessels after Myocardial Infarction - Riemenschneider, Sonja B. (Biomaterials, 2016)
A major goal of tissue engineering is the creation of pre-vascularized tissues that have a high density of organized microvessels that can be rapidly perfused following implantation. This is especially critical for highly metabolic tissues like myocardium, where a thick myocardial engineered tissue would require rapid perfusion within the first several days to survive transplantation. In the present work, tissue patches containing human microvessels that were either randomly oriented or aligned were placed acutely on rat hearts post-infarction and for each case it was determined whether rapid inosculation could occur and perfusion of the patch could be maintained for 6 days in an infarct environment. Patches containing self-assembled microvessels were formed by co-entrapment of human blood outgrowth endothelial cells and human pericytes in fibrin gel. Cell-induced gel contraction was mechanically-constrained resulting in samples with high densities of microvessels that were either randomly oriented (with 420±140 lumens/mm(2)) or uniaxially aligned (with 940±240 lumens/mm(2)) at the time of implantation. These patches were sutured onto the epicardial surface of the hearts of athymic rats following permanent ligation of the left anterior descending artery. In both aligned and randomly oriented microvessel patches, inosculation occurred and perfusion of the transplanted human microvessels was maintained, proving the in vivo vascularization potential of these engineered tissues. No difference was found in the number of human microvessels that were perfused in the randomly oriented (111±75 perfused lumens/mm(2)) and aligned (173±97 perfused lumens/mm(2)) patches. Our results demonstrate that tissue patches containing a high density of either aligned or randomly oriented human pre-formed microvessels achieve rapid perfusion in the myocardial infarct environment - a necessary first-step toward the creation of a thick, perfusable heart patch.